Knowledge, attitude, and preferred strategies towards HIV/AIDS prevention among adolescents attending secondary schools in South Western Uganda - Beebwa, Esther; Muzoora, Conrad; Ashaba, Scholastic; Groves, Sara; Atwine, Fortunate (African Health Sciences, 2021)
Background: Globally, HIV/AIDS continues to rise among adolescents. Ugandan studies have examined knowledge and attitudes regarding HIV/AIDS among adult populations. This study specifically paid attention to this particular age group of adolescents 12-19 years. Aim: To explore HIV knowledge and attitudes among adolescents attending secondary schools Mbarara Uganda. Methods: A qualitative descriptive study was conducted in three secondary schools in South Western Uganda. Fortyeight (48) adolescents with age range between 12-19 years were purposively recruited in the study. Data were collected from six focus groups and analyzed thematically. Ethical approval received from MUST (#05/10-17) and UNSCT (#SS4535) review committees. Results: Four themes emerged: Knowledge about HIV, sources of information, attitudes towards persons with HIV and prevention strategies. Most adolescents had the basic knowledge of HIV from multiple sources like social media, health workers, peers, and parents. Their attitudes toward individuals with HIV included compassion, shock, and uneasiness. Participants suggested prevention programs to be implemented in the schools emphasizing HIV education, life skills, sex education and the formation of peer groups. Conclusions: The findings showed that most participants had knowledge about HIV and how it can be prevented however few had knowledge gap thinking that HIV does not exist.
Keywords: Adolescents; Attitudes; Knowledge; HIV/AIDS; Prevention